Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian (Studi Pada Pelanggan Menggunakan Kartu Indosat Ooredoo Di Kecamatan Samarinda Ulu) - TaTghfirul Azhima Yoga Siswa3, Muhammad Nur1 Mardiana2 (EKONOMIA, 2020)
The purpose of this study were: 1). To determine the effect of the quality of products on purchase decisions on Indosat Ooredoo card customers in the District of Samarinda Ulu. 2) To determine the effect of price on purchase decisions on Indosat Ooredoo card customers in the District of Samarinda Ulu. 3) To determine the effect of promotion on purchase decisions on Indosat Ooredoo card customers in the District of Samarinda Ulu. 4) To determine the effect of product quality, price, and promotion on purchase decisions on Indosat Ooredoo card customers in the District of Samarinda Ulu. The theory used in this research is the quality of the product, price, promotion, consumer behavior and purchasing decisions.This research was conducted in Samarinda Ulu sub district. Samples taken as many as 100 respondents with a Non-Probability Samplingthe sampling technique used purposive sampling. Collecting data by questionnaires using Likert scale to measure each indicator. The analytical tool in the study using multiple linear regression analysisby using the tools of statistical program SPSS v20.The results of this study show that: 1) The variable quality of products significantly influence customer purchasing decisions Indosat Ooredoo card in the District of Samarinda Ulu, 2) Variable price significantly influencecustomer purchasing decisions Indosat Ooredoo card in the District of Samarinda Ulu, 3) Variable promotion not significant effect oncustomer purchasing decisions Indosat Ooredoo card in the District of Samarinda Ulu, 4) The variable quality of product, price, and promotion together - equally significant effect oncustomer purchasing decisions Indosat Ooredoo card in the District of Samarinda Ulu